Neurologic findings of vitamin B12 deficiency: presentation of 7 cases - Kalaycı, Ömer; Çetin, Mualla; Kırel, Birgül; Özdirim, Emire; Yetgin, Sevgi; Aysun, Sabiha; Gürgey, Aytemiz (The Turkish Journal of Pediatrics, 1996)
In this report, seven children, four males and three females, between the ages of five and 16 years with megaloblastic anemia and neuropsychiatric disorders are presented. Macrocytosis was identified in peripheral blood smears in all seven patients. Serum B12 levels were markedly reduced in four and were at the lower limit of normal in three patients. The Schilling test showed that B12 deficiency was due to specific cobalamin malabsorption in five and to inadequate dietary intake in two patients. Both neurological and hematological findings returned to normal after B12 replacement. This study shows that B12 deficiency should be considered in the differential diagnosis of neuropsychiatric disorders in children, including those with nonvegetarian habits, and that such patients should undergo a thorough hematological evaluation.